Enhanced Discriminative Fear Learning of Phobia-Irrelevant Stimuli in Spider-Fearful Individuals - Mosig, Carina; Merz, Christian J.; Mohr, Cornelia; Adolph, Dirk; Wolf, Oliver T.; Schneider, Silvia; Margraf, Jürgen; Zlomuzica, Armin (Frontiers in Behavioral Neuroscience, 2014)
Avoidance is considered as a central hallmark of all anxiety disorders. The acquisition and expression of avoidance which leads to the maintenance and exacerbation of pathological fear is closely linked to Pavlovian and operant conditioning processes. Changes in conditionability might represent a key feature of all anxiety disorders but the exact nature of these alterations might vary across different disorders. To date, no information is available on specific changes in conditionability for disorder-irrelevant stimuli in specific phobia (SP). The first aim of this study was to investigate changes in fear acquisition and extinction in spider-fearful individuals as compared to non-fearful participants by using the de novo fear conditioning paradigm. Secondly, we aimed to determine whether differences in the magnitude of context-dependent fear retrieval exist between spider-fearful and non-fearful individuals. Our findings point to an enhanced fear discrimination in spider-fearful individuals as compared to non-fearful individuals at both the physiological and subjective level. The enhanced fear discrimination in spider-fearful individuals was neither mediated by increased state anxiety, depression, nor stress tension. Spider-fearful individuals displayed no changes in extinction learning and/or fear retrieval. Surprisingly, we found no evidence for context-dependent modulation of fear retrieval in either group. Here we provide first evidence that spider-fearful individuals show an enhanced discriminative fear learning of phobia-irrelevant (de novo) stimuli. Our findings provide novel insights into the role of fear acquisition and expression for the development and maintenance of maladaptive responses in the course of SP.